Case Report: Bupropion Reduces the [123I]FP-CIT Binding to Striatal Dopamine Transporter - Milenkovic, Ivan; Bartova, Lucie; Papageorgiou, Konstantinos; Kasper, Siegfried; Traub-Weidinger, Tatjana; Winkler, Dietmar (Frontiers in Psychiatry, 2021)
The diagnosis of parkinsonian syndromes in patients with severe depression may be challenging due to overlapping clinical phenomena, especially regarding psychomotor and affective symptoms. [123I]FP-CIT-SPECT is a useful method to detect degenerative parkinsonian disorders. However, some drugs may influence the tracer binding and thus alter the result. We present a case of 56-year-old female inpatient with difficult-to-treat late-onset depression. Since the current major depressive episode was accompanied by psychotic features including delusions and hallucinations as well as hypokinesia, stooped posture and hypomimia, underlying degenerative parkinsonism was suspected. The pathologic [123I]FP-CIT-SPECT scan under ongoing antidepressant therapy with bupropion 300mg/die (serum level of bupropion 43 ng/ml and hydroxybupropion 2332 ng/ml) showed reduced FP-CIT binding throughout the striatum. The scan normalized upon a wash-out phase of four half-time periods (serum level of bupropion was 0.4 ng/ml and for hydroxybupropion 80.5 ng/ml). Our report should serve as a cautionary note for use of [123I]FP-CIT in depressed patients, particularly in those treated with drugs interfering with the dopamine transporters. Furthermore, our case argues for a need of consultation of a movement disorder specialist prior to dopamine transporter imaging.